2005
DOI: 10.1056/nejmoa042957
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Therapy with Adefovir Dipivoxil for HBeAg-Negative Chronic Hepatitis B

Abstract: In patients with HBeAg-negative chronic hepatitis B, the benefits achieved from 48 weeks of adefovir dipivoxil were lost when treatment was discontinued. In patients treated for 144 weeks, benefits were maintained, with infrequent emergence of viral resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
369
1
17

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(396 citation statements)
references
References 17 publications
9
369
1
17
Order By: Relevance
“…In another study [30], after a total of 3 years of lamivudine treatment, 56% of patients showed at least a 2-point improvement in histologic activity index scores, bridging fibrosis improved by at least 1 point in 63% and cirrhosis improved in 73% (score reduced from 4 to 3 or lower). Similar improvements in histology have been shown for adefovir [31] and entecavir [32,33] treatment also. These studies demonstrate that fibrosis, and even cirrhosis, are partially reversible with long-term nucleos(t)ide treatment that suppresses HBV DNA to low or undetectable levels.…”
Section: Hbvdna As a Prognostic Markersupporting
confidence: 76%
“…In another study [30], after a total of 3 years of lamivudine treatment, 56% of patients showed at least a 2-point improvement in histologic activity index scores, bridging fibrosis improved by at least 1 point in 63% and cirrhosis improved in 73% (score reduced from 4 to 3 or lower). Similar improvements in histology have been shown for adefovir [31] and entecavir [32,33] treatment also. These studies demonstrate that fibrosis, and even cirrhosis, are partially reversible with long-term nucleos(t)ide treatment that suppresses HBV DNA to low or undetectable levels.…”
Section: Hbvdna As a Prognostic Markersupporting
confidence: 76%
“…Genotypic resistance occurs in approximately 20% of patients per year in lamivudine treated patients 10,11 , and at a Villet 4 lower rate in adefovir treated patients, i.e. 3% at year two with a progressive increase to 29% at year five of therapy 12 .…”
Section: Chronic Hepatitis B Virus (Hbv) Infection Remains a Major Hementioning
confidence: 99%
“…Although resistance to ADV is slow to emerge, resistant variants increase progressively after the first year, reaching 29% in year five [16]. The advantages of ADV are its limited resistance during first two years, the absence of cross-resistance with LAM and other L-nucleosides and, therefore, its value as treatment for LAM-resistant CHB [17][18] and for hepatic decompensation associated with LAM resistance prior to and after liver transplantation [19].…”
Section: Section I: Published Results Based On the Consensus Of Eamentioning
confidence: 99%